Performance Characterization of Python Runtimes for Multi-device Task Parallel Programming - Ruys, William; Lee, Hochan; You, Bozhi; Talati, Shreya; Park, Jaeyoung; Almgren-Bell, James; Yan, Yineng; Fernando, Milinda; Erez, Mattan; Gligoric, Milos; Burtscher, Martin; Rossbach, Christopher J.; et al. (International journal of parallel programming, 2025)
Modern Python programs in high-performance computing call into compiled libraries and kernels for performance-critical tasks. However, effectively parallelizing these finer-grained, and often dynamic, kernels across modern heterogeneous platforms remains a challenge. This paper designs and optimizes a multi-threaded runtime for Python tasks on single-node multi-GPU systems, including tasks that use resources across multiple devices. We perform an experimental study which examines the impact of Python’s Global Interpreter Lock (GIL) on runtime performance and the potential gains under a GIL-less PEP703 future. This work explores tasks with variants for different different device sets, introducing new programming abstractions and runtime mechanisms to simplify their management and enhance portability. Our experimental analysis, using tasks graphs from synthetic and real applications, shows at least a 3 × (and up to 6 × ) performance improvement over its predecessor in scenarios with high GIL contention. Our implementation of multi-device tasks achieves 8 × less overhead per task relative to a multi-process alternative using Ray.